Nilai-Nilai Religius dalam Tembang Dolanan Anak sebagai Pembentuk Karakter Anak: Religious Values in Children's Toy Songs as Shaping Children's Characters - Suprapto; Rohmad Arkam; Moh. Zainul Arifin (Educan, 2025)
Indonesia is rich in culture, it is important to re-understand the oral traditions of the people. Instilling religious values ​​through tembang dolanan to build children's moral character is now a challenge and problem that is very urgent and cannot be avoided. Many of the current generation are not familiar with local culture such as children's folk songs. Children's dolanan songs are local cultural wisdom as a medium for forming children's character. Dolanan songs can be used as teaching materials to instill character education in students. Children's folk songs must be preserved from generation to generation. The aim of this research is to describe and explain the religious values ​​contained in tembang dolanan as a form of instilling character education in children. The research design uses a qualitative descriptive method, while the data collection technique uses literature study. The results of this research found religious values ​​in children's dolanan songs, values ​​that are in accordance with Javanese cultural norms. The religious values ​​in Tembang Dolanan have an influence on religious teachings, especially Islam. Second; Instilling religious values ​​through tembang dolanan can help students get to know themselves, their own culture and the cultures of other people, express language, discover and use the analytical and imaginative abilities that exist within themselves.